Biopolitical and Necropolitical Constructions of the Incarcerated Trans Body - Zhang, Christoph M. (Columbia Journal of Gender and Law, 2019)
This Article posits that the issue of gender-affirming genital surgery conjures competing constructions of the incarcerated trans body that reflect different conceptions of its relationship to state power. It offers a reading of this conflict as a clash between a biopolitical and a necropolitical conception of the incarcerated trans body. Biopolitics is a theory of state power that views the state as the arbiter and administrator of life and all life processes. Necropolitics, on the other hand, posits that sovereignty is defined by its power to mark out certain populations for social and literal death.